The Effectiveness Of Using Zoom Cloud Meeting Application Toward Improving Students’ Speaking Ability - Rahmi Pertiwi, Dian; Setiawati (Unit Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Agama Islam Hubbulwathan, Duri, Indonesia, 2023)
This research discusses The Effectiveness of using Zoom Cloud Meeting Application toward improving students’ speaking ability at the eleventh grade MIPA of SMA NEGERI 2 Mandau. The purpose of this research was to find how is The Effectiveness of Using Zoom Cloud Meeting Application Toward Improving Students’ Speaking Ability at the eleventh grade MIPA of SMA NEGERI 2 Mandau. The approach used a quantitative approach and the research design used correlation with a population of 209 students with a sample of 35 respondents obtained using the random sampling method. Measurement of the effectiveness of the using Zoom Cloud Meeting Application to improve students’ speaking ability is calculated through correlation analysis, hypothesis testing and effective testing. The correlation result show that the using Zoom Cloud Meeting Application is significantly effective in improving students’ speaking ability at The eleventh grade MIPA of SMA NEGERI 2 Mandau. The criterion for rejection of Ho is if a significant value α < 0,05 and Ha is accepted if a significant value α> 0,005, so because the result is accepted that is sig(2 tailed) 0,109 > 0,05. That is can be concluded that there is a relationship between Zoom Cloud Meeting Application is Effective to improve students’ speaking ability at the eleventh grade MIPA of SMA NEGERI 2 Mandau. So it can be concluded that the using Zoom Cloud Meeting Application toward improving students’ speaking ability at the eleventh grade MIPA of SMA NEGERI 2 Mandau with percentage of 77,6% from result Effective testing